Émotions épistémiques et créativité dans la formation enseignante : un duo gagnant ? - Catherine Audrin; Aleksandra Vuichard; Isabelle Capron Puozzo (Recherches en Éducation)
The importance of emotions, both positive and negative, in creativity has been highlighted in the literature. Nevertheless, in this context, few studies have been focusing on epistemic emotions. These refer to all affective states emanating from cognitive activities (Scheffler, 2010; Silvia, 2010) and particularly in a context of knowledge appropriation (Pekrun et al., 2017). This research aims to study 1) whether these emotions are involved in creative contexts and 2) if so, to which intensity. Data was collected during a course on creativity for future teachers. Participants were asked to participate to two creativity technics and to 1) keep a logbook to report the emotions they felt during these activities (Botella et al., 2017) and 2) to answer a questionnaire measuring the intensity of their epistemic emotions. Results suggest that participants actually experienced epistemic emotions during the creativity techniques. More specifically they felt curiosity, enthusiasm and, to a lesser extent, surprise. These results are corroborated by the logbooks, which further explain the emotional process felt in a creative context: while the first emotions felt were sometimes negative (such as fear or anxiety), these were transformed into positive emotions such as enjoyment or interest as the creative technique progressed.